How does Store Branded Lookalike Packaging Affect Competition in a Dyadic Supply Chain: A Consumer Confusion Perspective. (September 2022) - Zha, Yong; Guo, Xiaowei; Chen, Huaping; Ling, Liuyi
Highlights: We build a game-theoretical model to explore the competition between national brand and store brand in the presence of consumer confusion about lookalike packaging. The SB will be introduced only when the consumer quality preference difference is moderate. The retailer may prefer a mixed strategy by attracting low-end (high-end) consumers with national (store) brand. Consumer confusion may bring a win-win, lose-lose or win-lose situation for supply chain parties. Abstract: Store branded lookalike packaging resembling national brand product (NB) packaging creates confusion for consumers who are uncertain about their quality preference of the store brand product (SB). This paper presents a model for exploring the NB manufacturer's wholesale price decision, and the response of the SB retailer, considering consumer confusion. Consumers differ in their quality preferences for products and are classified into two groups: deliberate and confused, depending on whether they have precise quality preferences of the SB. We find that when facing a hybrid structure of consumers, the retailer will introduce the SB only when the quality preference difference between high- and low-end consumers is moderate. When the SB is offered, the retailer may not always benefit from targeting low-end consumers with the SB only; a mixed strategy by attracting low-end (high-end) consumers to the national (store) brand product can bring higher profit. Examining the effect of consumer confusion, we find that it may bring a win-win, lose-lose, or win-lose situation for the manufacturer and retailer, depending on the quality preference difference and proportion of high-end consumers. We then consider the case when being deliberate is a choice of the consumer, finding that the retailer will induce consumers to be deliberate only when the store brand quality is low. Consumer confusion will always create a win-win outcome for the manufacturer and retailer when (1) SB quality is higher than NB quality, (2) SB quality is endogenized, or (3) consumers are confused about their quality preference for both the NB and SB. The consumer surplus may be enhanced or weakened, depending on the retailer's market segmentation strategy. Our results reconcile some discrepancies between theoretical predictions and empirical findings regarding the impacts of consumer confusion about the SB derived from lookalike packaging on a two-echelon supply chain, and our insights are robust.